Focal muscle vibration and neurocognitive exercise improve function and reduce neuropathic pain after sciatic nerve injury: a case report assessment through gait analysis - Camerota, Filippo; Pocino, Naomi Francesca; Zangrando, Federico; Lucani, Alessia; Paoloni, Marco; Mangone, Massimiliano; Celletti, Claudia (Frontiers in Rehabilitation Sciences, 2025)
The sciatic nerve may be injured during total hip arthroplasty (THA). This complication can lead to severe neuropathic pain syndrome. This case report aims to investigate the effect of a combined treatment approach involving neurocognitive rehabilitation and focal mechanical vibrations in a patient affected by iatrogenic sciatic nerve injury and neuropathic pain following total hip arthroplasty (THA). The patient was followed over a total of 1 year, during which she underwent three cycles of 12-week neurocognitive physiotherapy, with weekly 1 h sessions, interspersed with two cycles of 1-week therapy involving only focal mechanical vibrations (fMV). She was also evaluated with a clinical scale and gait analysis. We have observed a significant reduction in the pain perceived by the patient, although not complete, but interestingly, the patient reported resolution of allodynia right after the first fMV session. Furthermore, the duration of the gait cycle approached more normal values. Overall, the combined treatment of neurocognitive rehabilitation and focal mechanical vibrations yielded positive results and contributed significantly to the reduction of chronic neuropathic pain in the patient. Simultaneously, the focal mechanical vibrations seem to provide crucial proprioceptive stimulation, promoting better motor control and further aiding in neuropathic pain reduction.